A systematic review of the histological and molecular changes in rotator cuff disease. Issue 7 (July 2012) - Dean, B. J. F.; Franklin, S. L.; Carr, A. J.
Abstract : Introduction: The pathogenesis of rotator cuff disease (RCD) is complex and not fully understood. This systematic review set out to summarise the histological and molecular changes that occur throughout the spectrum of RCD. Methods: We conducted a systematic review of the scientific literature with specific inclusion and exclusion criteria. Results: A total of 101 studies met the inclusion criteria: 92 studies used human subjects exclusively, seven used animal overuse models, and the remaining two studies involved both humans and an animal overuse model. A total of 58 studies analysed supraspinatus tendon exclusively, 16 analysed subacromial bursal tissue exclusively, while the other studies analysed other tissue or varying combinations of tissue types including joint fluid and muscle. The molecular biomarkers that were altered in RCD included matrix substances, growth factors, enzymes and other proteins including certain neuropeptides. Conclusions: The pathogenesis of RCD is being slowly unravelled as a result of the significant recent advances in molecular medicine. Future research aimed at further unlocking these key molecular processes will be pivotal in developing new surgical interventions both in terms of the diagnosis and treatment of RCD.